2006
DOI: 10.1111/j.1525-1438.2006.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined adjuvant cisplatin and ifosfamide chemotherapy and radiotherapy for malignant mixed mullerian tumors of the uterus

Abstract: The role of adjuvant therapy for malignant mixed müllerian tumors of the uterus has not been established. Our aim was to review our experience with sequential adjuvant therapy using cisplatin and ifosfamide chemotherapy and radiotherapy after surgical staging. A retrospective study of 43 patients from 1995 to 2004 was undertaken. Survival was calculated using the Kaplan-Meier method and compared by the log-rank test. The Cox proportional hazard regression model was used to assess the effect of treatment on sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…The authors reported that sequential treatment after surgery decreased mortality, as compared to patients taking RT or CT alone [ 13 ]. Similarly, Wong et al [ 14 ], who reported a protocol of cisplatin and ifosfamide-based CT along with RT in 43 patients, noted improved survival in patients who received both CT and RT. However, these two studies did not provide separate analysis for early or advanced stages of disease.…”
Section: Discussionmentioning
confidence: 87%
“…The authors reported that sequential treatment after surgery decreased mortality, as compared to patients taking RT or CT alone [ 13 ]. Similarly, Wong et al [ 14 ], who reported a protocol of cisplatin and ifosfamide-based CT along with RT in 43 patients, noted improved survival in patients who received both CT and RT. However, these two studies did not provide separate analysis for early or advanced stages of disease.…”
Section: Discussionmentioning
confidence: 87%
“…In this context, there have been several studies which have investigated the role of adjuvant therapy in uterine carcinosarcoma using multimodal approach since year 2000 [18-20]. These studies all show that treatment, which includes surgical operation, radiation therapy, and chemotherapy, increased the OS of uterine carcinosarcoma patients compared to treatment that only involves PORT or chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no consensus treatment guidelines related to improved survival outcomes. The rarity of this tumor limits the potential for large clinical trials [ 73 ]. Nevertheless, the persistent high mortality rate and high recurrence rate [ 73 ] with no significant improvement in patient survival during the past 40 years [ 24 ] demands the attention and time of researchers in a fight to improve treatment modalities and widen the understanding of uterine MMMT.…”
Section: Discussionmentioning
confidence: 99%